Seismic analysis of masonry buildings using explicit integration method - Mora, Elesban Nochebuena (2022)
The Finite Element Method (FEM) has become one of the most used numerical tools for advanced modelling of unreinforced masonry buildings. Implicit methods are often used to solve the set of equations in structural problems. Although they are reliable given their precision, the computational effort is high and strongly dependent on the convergence criteria. These difficulties increase when structural problems involve nonlinear dynamic responses, such as the seismic analysis of masonry buildings, where the quasi-brittle behaviour of the material hinders the convergence of the solution. Explicit methods can overcome this obstacle, as they were developed for mechanical problems with severe geometric and material discontinuities. The explicit solvers require a significantly small time increment to produce accurate results, leading to analyses with many thousands of steps, but with less computational effort. However, some parameters affect the stability of the solution and the accuracy of the results. This article addresses these parameters and their influence on the dynamic response of an unreinforced masonry building. Four FEM models were created using Abaqus/Explicit to perform a sensitivity analysis. The number and type of elements were varied (linear fully integrated elements and reduced integration elements with hourglass control), aiming at evaluating their effect on the energy balance, which is a parameter that controls the quality of the solution.